Review of O. V. Khaliman Monograph Grammar of Evaluation: Categories of the Ukrainian Language, Edited by T. A. Kosmenda. Kharkiv: Maidan, 2019 (Linguostylistic Studies, 2019)
Review  ofO. V. Khaliman. Monograph Grammar of Evaluation: Categories of the Ukrainian Language, Edited by T. A. Kosmenda. Kharkiv: Maidan, 2019